Concept Based Instruction: Enhancing Grammar Competence in L2 Learners. (August 2019) - Harun, Haliza; Abdullah, Norhana; Ab Wahab, Nursyuhada'; Zainuddin, Nurkhamimi
Over the past decades, much of the discussion regarding grammar teaching has evolved around the identification of the best language teaching approach to facilitate effective learning of English language among second language (L2) learners. Despite the various approaches introduced and implemented in the realm of L2 teaching, the language performances of these learners are still 'off-target' as they are still found not able to use the correct language expressions to serve their communicative needs. Investigation of the use of concepts in the learning and teaching of grammar may provide an alternative solution in enhancing learners' L2 grammar competence. Known as Concept Based Instruction (CBI) this pedagogical approach that is predicated on Vygotskian thought, centres on promoting the quality of the grammar rules in helping learners to understand and use the grammar concepts to achieve their communicative needs. This article focuses on the principles found in CBI with the aim of exploring CBI's potential and hence facilitate in-depth understanding of not only the structural forms but also the semantic meaning of the target language among L2 learners.